Transforming the Role of PGSD/PGMI Lecturers in Preparing Teacher Candidates Who Are Adaptive to Technological Disruption - Sari Nusantara Putri; Alfiansyah Alfiansyah; Achmad Tarmidzi Anas (LP2M IAI Al-Khairat Pamekasan, 2026)
The rapid advancement of digital technology has significantly transformed the landscape of education, demanding a fundamental shift in the roles of educators, particularly in teacher education programs. This study aims to analyze the transformation of lecturers’ roles in PGSD/PGMI in preparing prospective teachers who are adaptive to technological disruption. The research employs a qualitative approach with a descriptive case study design to explore in depth the practices, challenges, and strategies implemented by lecturers in integrating technology into the learning process. Data were collected through in-depth interviews, observations, and documentation, and analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings reveal that lecturers have undergone a significant role transformation from knowledge transmitters to facilitators, learning designers, and innovators. This transformation is reflected in the implementation of student-centered learning approaches, integration of digital technologies, and the emphasis on developing digital literacy and 21st-century skills among pre-service teachers. However, the study also identifies several challenges, including disparities in digital competence, limited technological infrastructure, and resistance to pedagogical change. The study concludes that the transformation of lecturers’ roles is essential in producing adaptive, innovative, and technologically competent teachers. Therefore, continuous professional development, institutional support, and strategic policy implementation are required to optimize the quality of teacher education in the era of technological disruption.